Highly thermostable mixed lanthanide organic frameworks with high quantum yield for warm white light-emitting diodes - Shen, Yanqiong; Pan, Xianyong; Zhao, Yaru; Gu, Qingchuan; Li, Qipeng (Frontiers in Chemistry, 2023)
A mixed lanthanide organic framework was prepared via hydrothermal methods using m-phthalic acid (m-H2BDC), 1,10-phenanthroline (1,10-Phen), and Ln3+ ions, formulated as [HNMe2][Eu0.095Tb1.905(m-BDC)3(phen)2] (ZTU-6). The structure and stability of ZTU-6 were characterised by X-ray diffraction (XRD) and thermogravimetric analysis (TGA), which revealed a three-dimensional pcu topology with high thermal stability. Fluorescence tests showed that ZTU-6 emitted orange light with a high quantum yield of 79.15%, and it can be effectively encapsulated in a light-emitting diode (LED) device emitting orange light. In addition, ZTU-6 was found to be compatible with BaMgAl10O17:Eu2+ (BAM) blue powder and [(Sr,Ba)2SiO4:Eu2+] silicate yellow and green powder to create a warm white LED with a high colour rendering index (CRI) of 93.4, a correlated colour temperature (CCT) of 3908 K, and CIE coordinates of (0.38, 036).